Characterization of metallic fuel for minor actinides transmutation in fast reactor. (January 2017) - Capriotti, L.; Brémier, S.; Inagaki, K.; Pöml, P.; Papaioannou, D.; Ohta, H.; Ogata, T.; Rondinella, V.V.
Abstract: The METAPHIX programme is a collaboration between the Central Research Institute of Electric Power Industry (CRIEPI, Japan) and the Joint Research Centre - Institute for Transuranium Elements (JRC-ITU) of the European Commission dedicated to investigate the safety and effectiveness of a closed nuclear fuel cycle based on Minor Actinides (MA: Np, Am, Cm) separation from spent fuel, incorporation in metal alloy fuel and transmutation in fast reactor. Nine Na-bonded experimental pins of metal alloy fuel were prepared at ITU and irradiated at the Phenix reactor (CEA, France) achieving 2.5 at.%, 7 at.% and 10 at.% burn-up. Four metal alloy compositions were irradiated: U-Pu-Zr used as fuel reference, U-Pu-Zr + 5 wt.% MA, U-Pu-Zr + 2 wt.% MA + 2 wt.% Rare Earths (RE: Nd, Y, Ce, Gd), and +5 wt.% MA + 5 wt.% RE, respectively. RE reproduce the expected output of a pyrometallurgical reprocessing facility. Post Irradiation Examination is performed using several techniques, covering properties ranging from the macroscopic morphology of the fuel matrix to the microanalysis of phases and elemental redistribution/segregation. The irradiated fuel is characterized by many phases occurring along the fuel radius. The fuel underwent large redistribution of the fuel constituents (U, Pu, Zr) and many secondary phases are present with a variety of compositions. The distribution of phases in the irradiated fuel containing minor actinides and rare earths is essentially similar to that observed in the basic ternary alloy fuel. Highlights: Demonstration of closed nuclear fuel cycle using metallic fuel and pyroprocessing. Electron Probe Micro Analysis on U-Pu-Zr metallic fuel. Redistribution of the main elements and phases identification. Minor actinides and Rare Earths segregate in secondary phases.